Environmental monitoring and competitive intelligence and their impact on the core capabilities of the organization - an exploratory study of the opinions of a sample of managers of the Karbala Cement Manufacturing Company - Akram Mohsen Mahdi Al - Yasiri; Ahmed Abdullah Amanh Alshammari (Iraqi Journal for Administrative Sciences, 2025)
This Research aimed at determining the influence of environmental scanningand competitive intelligence on the core competences of Iraqi Organizations . For this purpose the researcher has depended on the processes of environmental scanning ( scanning ,monitoring , forecasting , and evaluation ) according to ( Hitt et al , 2007 : 37)(Witcher&Chau , 2010 :90-91) (Dess et al ,2007 :43 ) , and depended on the processes of competitive intelligence (Planning , gathering , analyzing and dissemination) according to ( Santos &Correia , 2010:2) ( Dishman&Calof ,2008:768 - 770) ( Stratuss& Du Toit , 2010:306). The dimensions of core competences ( resources , capabilities , human capital ) that have been used are according to ( Jelassi and Enders , 2008 : 79 )(Bani – Hani and Al- Hawary , 2009 :98 ) and (Vincent and Focht , 2009 : 166 ). The Karbala Company for Manufacturing Cement has been chosen to verify this Research via a questionnaire ( 75) individuals of the managers of the company , in addition to personal interviews. The Spearman connection factor , and the ( t ) test to recognize the identity of this relation, and the ( f ) test to determine the identity of the regression equation , also the ( R2 ) has been used to explain the degree of the influence of the independent variable in the dependent variable . Some of the most important conclusions the study arrived at are that environmental scanning and competitive intelligence have a significant impact in the growth and competition of organizations through building core competences of the company that help in building sustainable competitive advantage and achieve strategic succeeded . The study has been concluded with a number of recommendations ,some of which are :  Focusing on the practice of the process of environmental scanning and competitive intelligence in the company in a wider scope in the light of Iraqi environment which is characterized by environmental uncertainty .  Consolidating the company 's resources and capabilities on all levels in a way that competitors find difficult to surpass.  Keeping a high level of skills and knowledge , and increasing the staff 's expertise in a way that gives the company a competitive advantage .